Pelecehan Seksual Melalui Aplikasi Tiktok - Salsabila Wijaya; Rizki Setiawan (GUIDING WORLD (BIMBINGAN DAN KONSELING), 2024)
Violence in Indonesia is increasing, especially sexual violence against women. The Ministry of Women's Empowerment and Child Protection in 2024, stated that women will be the dominant victims in cases of violence in 2024. One type of sexual violence that often occurs according to data obtained in the 2024 Online Information System for the Protection of Women and Children is sexual harassment. , which can occur without limitations of age, space and time. Sexual harassment is not only carried out in public spaces but can be done through social media, one of which is the TikTok application. This research aims to find out and explore the issue of sexual harassment through the TikTok application, using a descriptive qualitative approach and based on Kimberle Crenshaw's intersectionality theory, to find out how sexual harassment factors can influence a person's vulnerability to sexual harassment in cyberspace.